Anticancer activity of ethanolic extract of propolis on AGS cell line - Amini-Sarteshnizi Nematallah; Mobini-Dehkordi Mohsen; Khosravi-Farsani Somayeh; Teimori Hossein (Shahrekord University of Medical Sciences, 2015)
Introduction: Propolis is a natural product derived from various plant resins collected by honeybees, and has been used as a folk medicine for centuries. Propolis has been reported to exhibit a broad spectrum of activities including antibacterial, antifungal, antiviral, anti-inflammatory, antioxidant, hepatoprotective, and anticancer properties. The aim of this study was to investigate the effect of ethanolic extract of propolis (EEP) obtained from Dinaran area (Iran) on AGS human gastric cancer cell line. Methods: The ethanolic extract of samples was obtained by ethanol 96% and pure extract was dissolved in dimethyl sulfoxide (DMSO) and used for experiments. The cytotoxic effects of various concentrations of EEP on AGS cells were investigated by MTT assay test after 24, 48, and 72 hours and compared with control cells. Results: The EEP inhibited the growth and proliferation of AGS human gastric cancer cell line. The antiproliferative effects were revealed in a dose and time-dependent manner. The IC50 values were recorded as 60, 30, and 15 (μg/ml) in treatment times of 24, 48 and 72 hours, respectively. Conclusion: These findings indicated that the native EEP has strong antiproliferative effects against cancerous AGS cells. Thus, propolis and related products may provide a novel approach to the chemoprevention and treatment of human gastric cancer.